UNRAVELING THE BEST NON-PHARMACOLOGICAL INTERVENTIONS FOR COGNITIVE FUNCTION AND DEPRESSION IN ELDERLY WITH COGNITIVE IMPAIRMENT: A NETWORK META-ANALYSIS - Masykur, Umar Jundullah; Janet, Karensa Abby; Putri, Dwi Sandhi Aulia Pramesti; Jatmiko, Sarazata Indi Rozaany; Kurniawan, Shahdevi Nandar (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Emerging evidence suggests that non-pharmacological interventions can improve cognitive function and alleviate depressive symptoms in elderly individuals with cognitive impairment. However, the comparative effectiveness of these interventions remains unclear. Objective: This network meta-analysis (NMA) compares the efficacy of eight non-pharmacological interventions—Virtual Reality (VR) or Exergame, Computerized Cognitive Training (CCT), Mind-Body Exercise (MBE), Physical Exercise, Music or Art Therapy, Health Education, Treatment as Usual (TAU), and a Control group (no intervention, placebo)—on cognitive function and depression in elderly individuals with cognitive impairment. Methods: Randomized controlled trials (RCTs) published up to August 10, 2024, were systematically searched in Web of Science, PubMed, Embase, and Cochrane Library databases. A Frequentist random-effects network meta-analysis was conducted using R. Results: Total 46 RCTs with 3043 participants were included. The pooled results showed that CCT (SMD = 2.33, 95% CI [1.34, 3.32]), Physical Exercise (SMD = 2.24, 95% CI [1.24, 3.23]), and VR or Exergame (SMD = 2.09, 95% CI [1.10, 3.08]) significantly improved global cognition. VR or Exergame was also effective in enhancing attention (SMD = -3.49, 95% CI [-6.85, -0.14]), executive function (SMD = -75.54 (95% CI [-118.24, -33.04]), and reducing depressive symptoms (SMD = -2.62, 95% CI [-4.08, -1.15]). Conclusion: This NMA highlights the superior efficacy of CCT, Physical Exercise, and VR or Exergame in improving global cognition in elderly individuals with cognitive impairment. Additionally, VR or Exergame is particularly effective for enhancing attention, executive function, and reducing depressive symptoms, suggesting it should be integrated into cognitive rehabilitation programs.